2017
DOI: 10.1104/pp.16.01859
|View full text |Cite
|
Sign up to set email alerts
|

Starch Synthase 4 and Plastidal Phosphorylase Differentially Affect Starch Granule Number and Morphology

Abstract: The process of starch granule formation in leaves of Arabidopsis () is obscure. Besides STARCH SYNTHASE4 (SS4), the PLASTIDIAL PHOSPHORYLASE (PHS1) also seems to be involved, since double mutants lacking both PHS1 and the cytosolic DISPROPORTIONATING ENZYME2 (DPE2) displayed only one starch granule per chloroplast under normal growth conditions. For further studies, a triple mutant and various combinations of double mutants were generated and metabolically analyzed with a focus on starch metabolism. The mutant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
48
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(53 citation statements)
references
References 39 publications
5
48
0
Order By: Relevance
“…PTST2 was proposed to bind long malto-oligosaccharides with its carbohydrate-binding module and provide them as substrates to SS4 (Seung et al, 2017). This idea is broadly consistent with other observations that mutations affecting malto-oligosaccharide metabolism affect starch granule initiation (Malinova et al, 2017;Satoh et al, 2008;Seung et al, 2016).…”
supporting
confidence: 84%
See 1 more Smart Citation
“…PTST2 was proposed to bind long malto-oligosaccharides with its carbohydrate-binding module and provide them as substrates to SS4 (Seung et al, 2017). This idea is broadly consistent with other observations that mutations affecting malto-oligosaccharide metabolism affect starch granule initiation (Malinova et al, 2017;Satoh et al, 2008;Seung et al, 2016).…”
supporting
confidence: 84%
“…Rather, it appears to play a critical role in starch granule initiation: the Arabidopsis (Arabidopsis thaliana) ss4 mutant usually has zero, one, or rarely two or three granules per chloroplast (Roldán et al, 2007;Malinova et al, 2017), instead of five to seven granules found in most wild-type chloroplasts (Crumpton-Taylor et al, 2012). The total starch content at dusk is lower in this mutant, yet this starch is incompletely metabolized at night.…”
mentioning
confidence: 93%
“…Moreover, recent studies with the rice and barley Pho1 indicate that the enzyme is capable of producing and extending MOS solely from Glc1P (i.e., in the absence of α-glucan primer [302]. If SP plays a role in granule initiation, as indicated by these studies (and those of Malinova et al [254] in the above Section 5.2.2), it is not yet clear whether this is in concert with the SSIII/SSIV-mediated pathway or if the two pathways operate separately under different circumstances. It has been argued that SP and SBE activities acting in concert produce branched glucans resistant to phosphorolysis in the early stages of endosperm development and potential initiation points for granule synthesis to continue [302,362].…”
Section: Starch Phosphorylasesupporting
confidence: 50%
“…For a review of starch granule initiation the reader is referred to a review by D'Hulst and Mérida [252]. Recently, a role for plastidial starch phosphorylase (SP, see below) has been proposed for starch granule initiation in chloroplasts, in addition to SSIII and SSIV [253,254]. However, studies with ssIV mutants in the endosperm of japonica rice show very different effects on storage starch synthesis.…”
Section: Soluble Starch Synthasesmentioning
confidence: 99%
“…Of these genes, SS4 seems to play a predominant role in starch granule formation within the root apex and in root gravitropism. Recent work has also shown that the SS4 gene is important for regulating starch granule number in leaves (Malinova et al, 2017). Further work revealed that among SS isoforms, only SS4 contains a unique Nterminal region with several long coiled-coil motifs that have been implicated in protein-protein interactions.…”
Section: Discussionmentioning
confidence: 99%